2002
DOI: 10.1016/s0920-5632(01)01807-2
|View full text |Cite
|
Sign up to set email alerts
|

Singular gauge potentials and the gluon condensate at zero temperature

Abstract: We consider a new cooling procedure which separates gluon degrees of freedom from singular center vortices in SU (2) LGT in a gauge invariant way. Restricted by a cooling scale κ 4 /σ 2 fixing the residual SO(3) gluonic action relative to the string tension, the procedure is RG invariant. In the limit κ → 0 a pure Z(2) vortex texture is left. This minimal vortex content does not contribute to the string tension. It reproduces, however, the lowest glueball states. With an action density scaling like a 4 with β,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We point out, however, that it is useful to disentangle the information carried by center elements and coset fields, defined above, when the vacuum energy is investigated. In particular, it was found that -in the continuum limit -the center elements provide a contribution to the gluon condensate [48,49].…”
Section: Gluon Field On the Latticementioning
confidence: 99%
“…We point out, however, that it is useful to disentangle the information carried by center elements and coset fields, defined above, when the vacuum energy is investigated. In particular, it was found that -in the continuum limit -the center elements provide a contribution to the gluon condensate [48,49].…”
Section: Gluon Field On the Latticementioning
confidence: 99%